Oro-Dental Health and Primary Nephrotic Syndrome among Vietnamese Children - Hang Minh Luong; Tra Thu Nguyen; Huy-Thinh Tran; Phung Thi Tran; Phuong-Nga Nguyen; Huong Thu Nguyen; Duc Minh Nguyen; Hanh Tran Thi Duc; Son Minh Tong (MDPI AG, 2021)
Primary nephrotic syndrome (PNS) is common in children, affecting the soft and hard tissues of the oral cavity. This study aimed to investigate the percentage of dental caries, gingivitis, hypertrophic gingivitis, and developmental defects of enamel (DDE) in children with PNS. The association of PNS with these diseases and oral care behavior was also assessed. A total of 407 children with PNS and 407 age- and gender-matched controls were recruited. PNS was diagnosed based on blood and urinary tests. The Simplified Oral Hygiene Index (OHI-S), the Gingival Index (GI), the Gingival Overgrowth Index (GOI), the Decayed, Missing, and Filled Teeth Index (dmft/DMFT), and DDE were collected. The PNS patients showed significantly higher scores of OHI-S, GI, and dmft, and higher proportions of dental caries and DDE than those of the controls (p < 0.001). It is necessary to establish a periodic dental protocol for PNS patients to improve their oral health status.